Associations between omega-3 fatty acids and insulin resistance and body composition in women with polycystic ovary syndrome - Ling Lu; Xiaoqin Li; Lin Lv; Yao Xu; Baohua Wu; Chaolin Huang (Frontiers in Nutrition, 2022)
BackgroundPolycystic ovary syndrome (PCOS) is strongly associated with abdominal obesity and insulin resistance and effective approaches to nutrition (e.g., omega-3 fatty acids intake) might improve the cardiometabolic risk profile. This study aimed to examine the associations of dietary and serum omega-3 fatty acids with insulin resistance (IR) and body composition among PCOS patients.MethodsA total of 185 patients with PCOS were included in our analysis. Dietary information was collected through face-to-face interviews using a 102-item food frequency questionnaire (FFQ). Serum omega-3 fatty acid levels were measured with the gas chromatography method. Body composition was measured by both dual-energy X-ray absorptiometry (DXA) and bioelectrical impedance (BIA) methods. The multivariable linear regression model was applied to analyze the associations of dietary and serum omega-3 fatty acids with the levels of Homeostasis Model Assessment for Insulin Resistance (HOMA-IR) and body composition parameters among PCOS patients.ResultsOur results indicated that the dietary long-chain omega-3 polyunsaturated fatty acids (PUFA) intakes were negatively associated with HOMA-IR (β = –0.089, P = 0.040), fat mass (β = –0.022, P = 0.047), and body fat percentage (β = –0.026, P = 0.032). For serum biomarkers, higher total omega-3 PUFAs levels (β = –0.158, P = 0.021) and long-chain omega-3 PUFAs levels (β = –0.187, P < 0.001), particularly eicosapentaenoic acid (EPA) (β = –164, P = 0.011) and docosahexaenoic acid (DHA) (β = –0.158, P = 0.001) were also associated with decreased HOMA-IR. In addition, generally, dietary and serum long-chain omega-3 PUFA levels, DPA, and DHA levels were both positively associated with muscle mass measured by DXA; whereas serum total, long-chain and individual omega-3 PUFA levels (e.g., DPA, EPA, and DHA) were all negatively associated with fat mass and body fat percentage. These findings were further confirmed by the findings for body composition measured by the BIA method.ConclusionHigher levels of dietary and serum omega-3 PUFAs, particularly long-chain omega PUFAs (DPA and DHA), might have beneficial effects on metabolic parameters and body composition among PCOS patients.